Głęboko zatrzymany ząb 21 z zagięciem koronowo-korzeniowym - opis przypadku = Deeply retained dilacerated tooth 21 - case report - Piotr Osica; Aleksandra Szczepkowska; Anna Janas-Naze (Kazimierz Wielki University, 2017)
Osica Piotr, Szczepkowska Aleksandra, Janas-Naze Anna. Głęboko zatrzymany ząb 21 z zagięciem koronowo-korzeniowym - opis przypadku = Deeply retained dilacerated tooth 21 - case report. Journal of Education, Health and Sport. 2016;6(11):54-62. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163885 http://ojs.ukw.edu.pl/index.php/johs/article/view/3962         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016.       Głęboko zatrzymany ząb 21 z zagięciem koronowo-korzeniowym - opis przypadku Deeply retained dilacerated tooth 21 - case report     Piotr Osica1, Aleksandra Szczepkowska1, Anna Janas-Naze1   1Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze       Adres do korespondencji: Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: piotr.osica@umed.lodz.pl tel. 42 675 75 71     Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001       Streszczenie W pracy opisano przypadek 12 letniej dziewczynki z głęboko zatrzymanym zębem 21 z dilaceracją, czyli zagięciem koronowo-korzeniowym.   Słowa kluczowe: ząb zatrzymany, dilaceracja, opóźnione wyrzynanie   Abstract The article presents the case of 12 year old girl with deeply retained dilacerated tooth 21 with   Key words: retained tooth, dilaceration, delayed eruption.